Pharmacokinetics and safety of tadalafil in a paediatric population with pulmonary arterial hypertension: A multiple ascending‐dose study. Issue 10 (9th August 2019) - Small, David; Ferguson‐Sells, Lisa; Dahdah, Nagib; Bonnet, Damien; Landry, John; Li, Baohui
Abstract : Aims: To evaluate the pharmacokinetics and safety of once‐daily (QD) tadalafil in paediatric patients with pulmonary arterial hypertension (PAH) to establish an appropriate dose range for further research. Methods: This was an open‐label, multicentre, international, multiple‐ascending‐dose study. Patients aged ≥2 years were enrolled into 1 of 3 cohorts based on body weight: heavy‐weight (≥40 kg), middle‐weight (25 to <40 kg), and light‐weight (<25 kg). Each patient received tadalafil QD for 10 weeks: 5 weeks at a low dose, then 5 weeks at a high dose. The doses for each cohort were intended to produce plasma tadalafil concentrations within the range produced by 5–10 mg (for the low dose) or 20–40 mg (for the high dose) of tadalafil in adults with PAH. Area under the plasma concentration–time curve during 1 dosing interval (AUCτ ), maximum concentration, and apparent clearance were assessed throughout the trial, as were safety and tolerability. Results: The study enrolled 19 patients aged 2–17 years, weighing 9.9–76.0 kg. Tadalafil's median (range) steady‐state AUCτ at the high dose was 7243 (3131–13 088) ngh/mL across all patients. Concentrations were higher in no bosentan‐treated patients than in bosentan‐treated patients, but both populations were within the range of respective adult patients taking 20–40 mg QD. Tadalafil had an acceptable safety profile consistent with the known safety profile of tadalafil in adults. Conclusions: Tadalafil 40 mg QD for patients ≥40 kg, and 20 mg QD for patients <40 kg and aged ≥2 years, are suitable for further research in paediatric patients with PAH.